Islamic wealth management from a Maqasid-based perspective: a case study of Malaysia - Mohd. Zain, Nor Razinah; Hassan, Rusni (IIUM Institute of Islamic Banking and Finance (IIiBF), 2019)
The purpose of this chapter is to analyse the measures taken by Malaysian stakeholders in manifesting the concept of Islamic wealth management (IWM) throughout their Islamic financial services industry (IFSI) and the latest development in the Malaysian Islamic capital market (ICM). The analysis is made through a Maqāṣid based perspective. This is a conceptual research that depends on Islamic jurisprudential principles and legal doctrinal method where the legal sources are appreciated. At the same time, the reality of the IWM is traced throughout the IFSI and ICM in Malaysia. The research proposes that IWM needs to have holistic guidelines and policies which are consistent with the Maqāṣid-based perspective. This is important to ensure that the IWM is achieving the Sharī‘ah compliance in the wealth creation, wealth enhancement, wealth protection and wealth distribution. It is identified that the Malaysian regulator authorities in IFSI and ICM are efficient in promoting IWM. This is done either directly or indirectly by the selected stakeholders. Additionally, it is attributed to the strong Malaysian legal framework in IFSI and ICM. The authors propose a theoretical model in achieving the Maqāṣid al-Sharī‘ah. In following this research, the relevant stakeholders especially the regulatory authorities of IFSI and ICM will find that the Maqāṣid-based perspective is important in achieving the Sharī‘ah compliant in relation to IWM. The research will be effective in solving Sharī‘ah-compliant issues in relation to IWM. This research identifies the Maqāṣid based perspective in relation to IWM, with examples from a case study of Malaysia.